Barley β-glucosidase: Expression during seed germination and maturation and partial amino acids sequences - Simos, George; Panagiotidis, Christos A.; Skoumbas, Angelos; Choli, Dora; Ouzounis, Christos; Georgatsos, John G. (Biochimica et biophysica acta. General subjects, 1994)
Unlike most of the hydrolytic enzymes that participate in endosperm mobilization, β-glucosidase of barley ( Hordeum vulgare) seeds does not increase during germination, even in the presence of exogenously added gibberellic acid. However, the germination process affects the physical properties of β-glucosidase in terms of charge and apparent molecular weight. Analysis of developing barley grains shows that the enzyme is synthesized two weeks before maturation and is stored in the endosperm of the dry dormat seed. Partial amino acid sequencing of the purified β-glucosidase demonstrates significant similarity between the barley enzyme and β-glycosidases that belong to family 1 of glycosyl hydrolases.